iPhone : the missing manual - Pogue, David, 1963- (Sebastopol, Calif. : O'Reilly, 2010)
Explains how to use the pocket computer - cellular phone with iPod, internet and camcorder in addition to video calling and 240,000 add-on apps.
Includes index.
'Covers all models with 4.0 software - including the iPhone 4.' -- Cover.
Previous ed.: Sebastopol, Calif.: O'Reilly Media, 2009.
Keywords: iPhone (Smartphone); Digital music players; Pocket computers; Cell phones